2020
DOI: 10.1093/brain/awaa125
|View full text |Cite|
|
Sign up to set email alerts
|

A venous mechanism of ventriculomegaly shared between traumatic brain injury and normal ageing

Abstract: Recently, age-related timing dissociation between the superficial and deep venous systems has been observed; this was particularly pronounced in patients with normal pressure hydrocephalus, suggesting a common mechanism of ventriculomegaly. Establishing the relationship between venous drainage and ventricular enlargement would be clinically relevant and could provide insight into the mechanisms underlying brain ageing. To investigate a possible link between venous drainage and ventriculomegaly in both normal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 64 publications
0
19
1
1
Order By: Relevance
“…Aso et al have investigated a possible link between venous drainage and ventricular enlargement in both normal and accelerated aging ( Aso et al, 2020 ). They found that changes encountered in cerebral venous drainage stems from venous insufficiency occur in normal aging processes.…”
Section: Ventricular Aging Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aso et al have investigated a possible link between venous drainage and ventricular enlargement in both normal and accelerated aging ( Aso et al, 2020 ). They found that changes encountered in cerebral venous drainage stems from venous insufficiency occur in normal aging processes.…”
Section: Ventricular Aging Mechanismsmentioning
confidence: 99%
“…They found that changes encountered in cerebral venous drainage stems from venous insufficiency occur in normal aging processes. They motivate ventricular enlargement to result from this change in the venous drainage pattern as well as cerebral atrophy ( Aso et al, 2020 ). This agrees with work by Apostolova et al that link ventricular enlargement to parenchymal volume loss following the progressive loss of neurons and de-arborization of the dendritic network ( Apostolova et al, 2012 ).…”
Section: Ventricular Aging Mechanismsmentioning
confidence: 99%
“…For example, compared with healthy controls, patients with iNPH showed increased FA, MD, and AD in the periventricular section of the CST (Hattingen et al, 2010 ; Hattori et al, 2012 ; Saito et al, 2020 ); decreased FA; and increased RD in the upper section of the CST and corpus callosum (Kanno et al, 2011 ; Saito et al, 2020 ), which may result from the mechanical force exerted by the abnormal ventriculomegaly on the surrounding tissues. Aso et al suggested that one of the mechanisms of ventricular enlargement is that changes in the venous drainage pattern could result in CSF absorption disorder in patients with iNPH (Aso et al, 2020 ). Kamiya et al ( 2017 ) reported an increased orientational coherence at the CST in patients with iNPH after CSF shunt surgery, which supports the oppression of periventricular tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular enlargement is accompanied by an increase in the space between folds and loss of gyrification (Hamelin et al, 2015;Aso et al, 2020). This feature is less prominent on medical images, but is another indicator for the significant topological changes of the brain (Plocharski et al, 2016;Shen et al, 2018).…”
Section: Sulcal Widening and Loss Of Gyrificationmentioning
confidence: 99%